Techno-predation – a contemporary phenomenon jeopardizing innovation networks all over the world. (2nd November 2019) - Mesly, Olivier
Abstract : The sudden and unwelcome appropriation or use of a new technology by a stakeholder (hereafter called the 'techno-predator') in an innovation network to the detriment of the creator of said technology (hereafter named the 'techno-prey') is called 'techno-predation.' This phenomenon may take many forms and involves various stakeholders (investors, companies, universities, researchers, inventors, or a mix of the five). Techno-predation follows a clearly identifiable pattern that usually takes place in innovation networks. It is particularly evident in the case of small businesses, which may not have the financial means to protect themselves against techno-predators. It may also be the fate of inexperienced universities or various institutions that are unwilling or unable to protect their researchers. Understanding techno-predation is one way of counteracting its negative or even devastating effects on innovation networks and society at large.